Oscillatory Flow Reactor Design for Biological Process - Norfaezahtul, Azaini; N., Masngut (Penerbit UMP, 2017)

(untitled)
Oscillatory flow reactor (OFR) is a novel type of tubular reactor consisting of equally spaced orifice baffles (sometimes called doughnut baffles) fitted inside the column of the reactor. OFR can be used for biological and chemical processes such as crystallisation of paracetamol, biofuel production, and production of sterols in ester saponification reactions. The aim of the study is to design and fabricate the oscillatory flow reactor for the purpose of biological process. In order to achieve turbulence flow inside the reactor, parameters such as reactor, baffles dimension, and type of oscillation system were considered prior to the design work. Autodesk: AutoCAD® 2016 was used to draw the reactor parts. The OFR was fabricated in the Faculty of Chemical and Natural Resources Engineering (FKKSA) workshop in Universiti Malaysia Pahang (UMP). A complete OFR consists of three main parts which are reactor column, baffles plate and oscillation system. The OFR column was made from 304 grade stainless steel with dimensions of 500 mm in height and 60 mm internal in diameter so that it can fit in an autoclave and can withstand high temperatures and pressures. Due to the OFR’s capability of mixing and transferring oxygen in gas-liquid phase, it was be further tested to evaluate its capability as bioreactor including the characterisation test based on its ability to maintain sterility, fluid loss due to evaporation, and the temperature profile.